2017
DOI: 10.1038/s41598-017-16263-y
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of microRNAs as potential cellular monocytic biomarkers in the early phase of myocardial infarction: a pilot study

Abstract: MicroRNA has been increasingly suggested to be involved in vascular inflammation. The aim of this study was to assess the expression profile of miRs as possible novel cellular biomarkers in circulating monocytes in patients with ST-segment elevation myocardial infarction (STEMI). Microarray techniques and TaqMan polymerase chain reaction were used to analyse the global expression of 352 miRNAs in peripheral blood monocytes from healthy donors (n = 20) and patients (n = 24) with acute STEMI. The expression leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 47 publications
2
24
0
1
Order By: Relevance
“…In accordance to our results, the 12 overexpressed miRNAs in the case-control study, were identified as significantly upregulated in individuals with AMI or CAD in previous studies [45,[49][50][51][52], or after cardiac ischaemia in animal models (miR-15 family) [53].…”
Section: Case-cohort Studysupporting
confidence: 92%
See 1 more Smart Citation
“…In accordance to our results, the 12 overexpressed miRNAs in the case-control study, were identified as significantly upregulated in individuals with AMI or CAD in previous studies [45,[49][50][51][52], or after cardiac ischaemia in animal models (miR-15 family) [53].…”
Section: Case-cohort Studysupporting
confidence: 92%
“…These miRNAs have been associated with 1) apoptosis in ECs and cardiomyocytes (has-miR-16-5p, has-miR-499a-5p, has-miR-21-5p, has-miR-22-3p, and has-miR-125b-5p) [54][55][56][57]; 2) proliferation and differentiation in VSMCs and cardiomyocytes (has-miR-145-5p, has-miR-143-3p, and has-miR-133a-3p) [49,58,59]; 3) angiogenesis (has-miR-222-3p, and has-miR-22-3p) [58]; 4) secretion of pro-inflammatory cytokines (has-miR-186-5p, All rights reserved. No reuse allowed without permission.…”
Section: Case-cohort Studymentioning
confidence: 99%
“…11 And study identified circulating monocytes as novel biomarkers and carriers for the cell-specific transfer of miRNAs in the early stage of myocardial infarction. 39 Some findings strengthen the potential of applying miRNAs, such as miR-708, to reconstitute lost cardiomyocytes in injured hearts and may provide a novel candidate for promoting heart regeneration. 40 Therefore, with further improving the miRNA detection technology, miRNA may become a marker for early diagnosis and treatment of AMI.…”
Section: Discussionmentioning
confidence: 79%
“…A study has revealed an important role of miRNAs as biomarkers of AMI and its associated symptoms, and their role in disease diagnosis, platelet activation monitoring, and prognostic outcome prediction . And study identified circulating monocytes as novel biomarkers and carriers for the cell‐specific transfer of miRNAs in the early stage of myocardial infarction . Some findings strengthen the potential of applying miRNAs, such as miR‐708, to reconstitute lost cardiomyocytes in injured hearts and may provide a novel candidate for promoting heart regeneration .…”
Section: Discussionmentioning
confidence: 91%
“…In addition, the expression level of mir-1 in peripheral blood of ACS patients was higher than that of non-ACS patients, and the expression level of miR-1 in UA patients was significantly higher than that of NSTEMI [15]. Although the expression level of miR-1 in the peripheral blood plasma or serum of AMI patients was increased, the expression level of miR-1 in the circulating monocytes of STEMI patients was significantly decreased [16]. The reason for this difference may be due to the cellular source of miR-1.…”
Section: Resultsmentioning
confidence: 89%